Civil Society and Peace: Local Civil Society Engagement in South Sudan's Peace Efforts - Ginanjar, Wahyu Rozzaqi (Nation State: Journal of International Studies, 2022)
South Sudan is one of the countries that has been hit by internal conflict since its independence in 2011. This article basically describes the involvement of civil society in peace negotiations in South Sudan. Using the literature study method and through the concepts of civil society and peace, this article reviews and analyzes the extent to which local civil society is involved in the peace negotiation process in South Sudan. This article has a finding that civil society participation in peace efforts in South Sudan is quite high, but not significant. This is an implication of the conflict pattern which tends to be structural. On the other hand, limited resources, both technical and material, are a major obstacle in relation to the ability of civil society in South Sudan to engage in peace efforts. Thus, as far as civil society is involved in peace efforts in South Sudan, their presence is only a mere formality, while the main decision remains with the political elites in South Sudan.